Semiotic analysis of the poetry "Morgenlied" by Martin Opitz - Prilimercy E. Kojongian (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
A This study aims to examine the sign system in the form of icons, indexes, and symbols and to interpret the meanings and messages as well as moral-religious values contained in the poem "Morgenlied" by Martin Opitz. The method used is a content analysis method with a qualitative approach based on semiotic analysis. This method serves to examine the poem "Morgenlied" by Martin Opitz, especially on the sign system in the form of icons, indexes, and symbols as well as religious moral values contained in the poem. While the data collection technique is a literature study. Based on the semiotic analysis, this poem contains a religious element in the form of a prayer of thanksgiving to God for His mercy and glory.